Clinical Examination and Self-Reported Upper Extremity Impairments in Patients with Long-Standing Type 1 Diabetes Mellitus. (11th March 2020) - Gutefeldt, Kerstin; Lundstedt, Simon; Thyberg, Ingrid S. M.; Bachrach-Lindström, Margareta; Arnqvist, Hans J.; Spångeus, Anna
Abstract : Aim . The aims of the current study were (1) to determine the prevalence of upper extremity impairments (UEIs) in patients with type 1 diabetes by clinical investigation; (2) to investigate if self-reported impairments were concordant with clinical findings and if key questions could be identified; and (3) to investigate if answers to our self-reported questionnaire regarding UEIs are reliable. Methods. Patients with type 1 diabetes were invited to participate in a cross-sectional study of clinical and self-reported (12 items) UEIs in adjunction to ordinary scheduled clinical visit. Before the visit, a questionnaire on UEIs was filled in twice (test-retest) followed by clinical testing at the planned visit. Results . In total, 69 patients aged 45 ± 14 years and with diabetes duration 26 ± 15 were included in the study. In the clinical examination, two-thirds (65%) of the patients showed one or more UEI, with failure to perform hand against back as the most common clinical finding (40%) followed by positive Phalen's test (27%), Tinel's test (26%), and Prayer's sign (24%). UEIs observed by clinical examination were often bilateral, and multiple impairments often coexisted. Self-reported shoulder stiffness was associated with impaired shoulder mobility and with Prayer's sign. Self-reported reduced hand strength was associated to lower grip force, Prayer's sign, trigger finger, fibrosis string structures, and reduced thenar strength as well as reduced shoulder mobility. In addition, self-reporting previous surgery of carpal tunnel and trigger finger was associated with several clinical UEIs including shoulder, hand, and finger. The test-retest of the questionnaire showed a high agreement of 80-98% for reported shoulder, hand, and finger impairments. Conclusion . UEIs are common in type 1 diabetes. Self-reported shoulder stiffness and reduced hand strength might be used to capture patients with UEIs in need of clinical investigation and enhanced preventive and therapeutic strategies, as well as rehabilitative interventions.